2015
DOI: 10.1097/md.0000000000002032
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Acute Kidney Injury Following Mannitol Infusion in Patients With Acute Stroke

Abstract: Mannitol, an osmotic diuretic, is commonly used to treat patients with acute brain edema, but its use also increases the risk of developing acute kidney injury (AKI). In this study, we investigated the incidence and risk factors of mannitol-related AKI in acute stroke patients.A total of 432 patients (ischemic stroke 62.3%) >20 years of age who were admitted to the neurocritical care center in a tertiary hospital and received mannitol treatment were enrolled in this study. Clinical parameters including the sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 25 publications
1
60
2
4
Order By: Relevance
“…The present study is in accordance with this. Finally, according to previous studies [15,16,36], AKI was significantly associated with an increased risk of mortality in patients with stroke, but in the present analysis, AKI was not an independent risk factor for adverse short-term outcomes.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The present study is in accordance with this. Finally, according to previous studies [15,16,36], AKI was significantly associated with an increased risk of mortality in patients with stroke, but in the present analysis, AKI was not an independent risk factor for adverse short-term outcomes.…”
Section: Discussioncontrasting
confidence: 38%
“…High NIHSS and APACHE II scores at ICU admission reflected the severity of illness. A retrospective study [36] AKI, acute kidney injury; CKD, chronic kidney disease; NIHSS, National Institutes of Health Stroke Scale; GCS, Glasgow Coma Scale; APACHE II, acute physiology and chronic health evaluation; sCr, serum creatinine; sCysC, serum cystatin C; β2-MG, β2-microglobulin; eGFR, estimated glomerular fltration rate; BUN, blood urea nitrogen. showed that high NIHSS score, low baseline eGFR, and hypertension were risk factors for AKI in stroke patients admitted to the Neurology ICU, and this was verified in the present multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment of choice for swelling is primarily mannitol, lactulose and diuretics. However, mannitol may cause acute kidney injury (2), lactulose can cause the metabolism of blood sugar and electrolyte (3) and the effects of diuretics for local inflammatory edema are poor (4). …”
Section: Introductionmentioning
confidence: 99%
“…У випадках, коли є затримка рідини в організмі й порушення фільтрації в нирках, побіч-ні ефекти манітолу можуть переважити діуретичний ефект. Особливо небезпечне застосування манітолу в пацієнтів, які страждають від хронічної ниркової недостатності й застійної серцевої недостатності: гостра гіперволемія може призвести до декомпенса-ції серцевої діяльності й набряку легень [7,15].…”
unclassified